2015
DOI: 10.1371/journal.pone.0130822
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fos-Like Immunoreactivity, Catecholaminergic and Serotoninergic Neurons Activated by the Laryngeal Chemoreflex in the Medulla Oblongata of Rats

Abstract: The laryngeal chemoreflex (LCR) induces apnea, glottis closure, bradycardia and hypertension in young and maturing mammals. We examined the distribution of medullary nuclei that are activated by the LCR and used immunofluorescent detection of Fos protein as a cellular marker for neuronal activation to establish that the medullary catecholaminergic and serotoninergic neurons participate in the modulation of the LCR. The LCR was elicited by the infusion of KCl-HCl solution into the laryngeal lumen of adult rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…These data clearly argue for two anatomically distinct airway sensory processing pathways that may form an anatomical framework for functional distinctions between respiratory reflex production and the conscious perception of airway irritations. For example, reflexive cough is a brainstem-mediated process that requires sensory input into the nTS and subsequent alterations to the activity of respiratory cells located in nuclei of the ventral and pontine respiratory groups (Baekey et al, 2003, Poliacek et al, 2009, Mazzone et al, 2011, Smith et al, 2013, Dutschmann et al, 2014, Koshiya et al, 2014, Zoccal et al, 2014, Ferreira et al, 2015, Wang et al, 2015. On the other hand, the central mechanisms that underpin the conscious perception of airway sensations leading to voluntary respiratory behaviours are less well understood and could conceivably be linked to the understudied somatic representation of airway sensation in the brain that is seemingly carried by the jugular-Pa5 circuitry.…”
Section: Neuroanatomy Of Airway Sensationmentioning
confidence: 99%
“…These data clearly argue for two anatomically distinct airway sensory processing pathways that may form an anatomical framework for functional distinctions between respiratory reflex production and the conscious perception of airway irritations. For example, reflexive cough is a brainstem-mediated process that requires sensory input into the nTS and subsequent alterations to the activity of respiratory cells located in nuclei of the ventral and pontine respiratory groups (Baekey et al, 2003, Poliacek et al, 2009, Mazzone et al, 2011, Smith et al, 2013, Dutschmann et al, 2014, Koshiya et al, 2014, Zoccal et al, 2014, Ferreira et al, 2015, Wang et al, 2015. On the other hand, the central mechanisms that underpin the conscious perception of airway sensations leading to voluntary respiratory behaviours are less well understood and could conceivably be linked to the understudied somatic representation of airway sensation in the brain that is seemingly carried by the jugular-Pa5 circuitry.…”
Section: Neuroanatomy Of Airway Sensationmentioning
confidence: 99%
“…Following experimental seizures, c‐fos immunoreactivity in TH‐IR neurones in the VLM and dorsal vagal complex mirrored that observed following hypoxia (17) and was similar to the distribution following experimentally induced hypotension; this could suggest that seizures themselves directly induce TH neuronal activity. C‐fos expression was also noted in NTS and VLM TH and serotonergic neurones following induction of the protective laryngeal chemoreflex which induces respiratory inhibition, bradycardia, and hypertension (44). A previous post‐mortem study of sudden unexplained death, showed c‐fos‐expressing neurones in the dorsal medulla (hypoglossal nucleus and/or the dorsal vagal nucleus) but not in control groups (13).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that involvement of the laryngeal chemorefl ex would explain the reported results. This refl ex induces specifi c response initiated by receptors in the laryngeal lumen and among its numerous eff ects, a signifi cant increase in blood pressure has been attributed to it [9,10,11,12]. Presumably, during intubation in patients with advanced laryngeal cancer, there is a signifi cant mechanical compression on the endolarynx and respectively, on the tumor mass, because of the obstructed lumen, which could cause an induction of the laryngeal chemorefl ex.…”
Section: Discussionmentioning
confidence: 99%